A review on customizing edible food materials into 3D printable inks: Approaches and strategies. (January 2021) - Pulatsu, Ezgi; Lin, Mengshi
Abstract: Background: Additive manufacturing (AM) is an emerging technology that has been a subject of interest in many areas, including agriculture and food science. AM technology can be used in three-dimensional (3D) food fabrication in an additive manner based on computer-aided design (CAD) data. 3D food printing technology offers many advantages over traditional methods: rapid prototyping without using molds or casts, providing customized foods, creating foods with complex shapes and structures, personalized nutrition, high efficiency, and low cost of production. It is crucial to have a systematic approach for food printings and redefine the printability to use a wide range of food materials. Scope and approach: This review article summarizes recent advances in 3D food printing with a focus on current approaches to define the printability and optimize the food ink formulas, the mechanisms of AM technology, and the suitability of food materials as precursors for 3D printing (3DP). The major steps associated with 3DP technology from the food perspective are elucidated in this review, which involve various approaches and strategies of 3DP. Key findings and conclusions: A systematic manufacturing approach is essential for a better understanding of the 3DP process rather than focusing on the machine parts. Framing each step in the 3DP and depicting the workflow suitable for food printings may simplify the research steps and accelerate high-quality 3DP for the food applications. Redefining the printability and summarizing existing approaches to obtain printable food materials will lay the foundation for future studies. Highlights: 3DP concept has been reviewed from the perspective of manufacturing systems. A detailed workflow and checkpoints are elucidated based on extrusion-based 3DP. The contents of food ingredients and food matrix affect the printability. Tailoring foods for 3DP can change the attributes of the fabricated food products.